Learning Individual Counseling Practicum Courses in Using Google Classroom-based LMS (Learning Management System). - Nuzliah; Mawaddah, Sri (CV Kalimasada Group, 2025)
Purpose - The individual counseling course is one of the courses that must be mastered by lecturers and students both online and offline. The aim of this research is to produce a product in the form of an Individual Counseling guidebook in the use of a Google Classroom-based LMS that can be used by lecturers and students of the BK Study Program in the BK Study Program in UIN Ar-Raniry and IAIN Lhoksemawe which are appropriate in terms of material and appearance, Describe the level of use of the Individual Counseling guidebook which can be used by BK lecturers and students as a learning reference. Design/Methodology/Approach - Method The research used is development research by following the development steps of the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research data were analyzed using descriptive statistical analysis and inferential statistics. Findings -The research results showed that (1) The individual counseling learning guidebook through the Google Classroom-based LMS (Learning Management System) is suitable for use by BK lecturers and BK students, (2) the level of use of the individual counseling learning guidebook through the Google Classroom-based LMS (Learning Management System) is good for use in individual counseling practice.. Originality/Value -The resulting individual counseling learning guidebook via Google Classroom-based LMS is declared feasible and can be used by BK Lecturers and BK Students to facilitate the teaching and learning process in individual counseling courses